2018
DOI: 10.1039/c7fd00175d
|View full text |Cite
|
Sign up to set email alerts
|

Determining the composition of the vacuum–liquid interface in ionic-liquid mixtures

Abstract: The vacuum–liquid interfaces of a number of ionic-liquid mixtures have been investigated using a combination of RAS-LIF, selected surface tension measurements, and molecular dynamics simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
73
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(89 citation statements)
references
References 74 publications
15
73
1
Order By: Relevance
“…This behavior is in contrast to the situation for neat [C 4 C 1 Im][PF 6 ] in Figure a and for neat ILs with longer alkyl chains, and indicates that the alkyl chains in the mixtures studied here are depleted from the liquid/vacuum interface. The driving force is a competing effect between the fluorinated chain of the [PFBMIm] + cation and the non‐fluorinated side chain of the [C 4 C 1 Im] + cation: The selective enrichment of the [PFBMIm] + cations is attributed to a (typically) larger surface tension of ILs with an alkyl chain compared to a fluorinated chain …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior is in contrast to the situation for neat [C 4 C 1 Im][PF 6 ] in Figure a and for neat ILs with longer alkyl chains, and indicates that the alkyl chains in the mixtures studied here are depleted from the liquid/vacuum interface. The driving force is a competing effect between the fluorinated chain of the [PFBMIm] + cation and the non‐fluorinated side chain of the [C 4 C 1 Im] + cation: The selective enrichment of the [PFBMIm] + cations is attributed to a (typically) larger surface tension of ILs with an alkyl chain compared to a fluorinated chain …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, investigations of the topmost layers of IL mixtures are getting more into the focus of research. A variety of studies has been performed, using reactive‐atom scattering with laser‐induced fluorescence detection (RAS‐LIF), neutron scattering, small‐angle X‐ray scattering and X‐ray reflectivity, time of flight secondary ion mass spectrometry (TOF‐SIMS), Rutherford backscattering spectroscopy (RBS), low‐energy ion scattering (LEIS), X‐ray photoelectron spectroscopy (XPS) and molecular dynamics (MD) simulations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface composition of binary IL mixtures with non‐functionalized imidazolium‐based ILs was investigated using various surface science techniques such as time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS),21,22 low‐energy ion scattering (LEIS),23,24 Rutherford backscattering (RBS),22,25, 26, 27 angle‐resolved X‐ray photoelectron spectroscopy (ARXPS),28, 29, 30 reactive atom scattering‐laser‐induced fluorescence (RAS‐LIF),20,31 and by simulations 20,26,32,33…”
Section: Introductionmentioning
confidence: 99%
“…The same [C 2 C 1 Im] 1‐x [C 12 C 1 Im] x [Tf 2 N] mixture as well as a mixture with a fluorinated side chain were recently investigated by RAS‐LIF combined with MD simulations 31. It was shown that the component with the lower surface tension is preferentially located at the surface of the mixture.…”
Section: Introductionmentioning
confidence: 99%